2018
DOI: 10.1038/s41419-018-0920-3
|View full text |Cite
|
Sign up to set email alerts
|

SIRT2 is required for efficient reprogramming of mouse embryonic fibroblasts toward pluripotency

Abstract: The role of sirtuins (SIRTs) in cancer biology has been the focus of recent research. The similarities between underlying pathways involved in the induction of pluripotent stem cells and transformation of cancer cells revealed the role of SIRTs in cellular reprogramming. Seven SIRTs have been identified in mammals and downregulation of SIRT2 was found to facilitate the generation of primed pluripotent stem cells, such as human induced pluripotent stem cells. Herein, we evaluated the role of SIRT2 in naive plur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The human Sirt2 protein, a homolog of the budding yeast silent information regulator 2 (Sir2), is a member of the Sirtuin family of NAD + -dependent deacetylases and ADP-ribosyltransferases [ 1 , 2 ]. Accumulating evidence has revealed that Sirt2 plays an important role in multiple cell events [3] , [4] , [5] , which involve a variety of biological and pathological conditions, including development, neural activity, obesity, and carcinogenesis [ 2 , 6 , 7 ]. Accordingly, various Sirtuin inhibitors have been developed and assessed for their effects on different diseases by targeting specific protein structures, biological activities, or signaling pathways [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human Sirt2 protein, a homolog of the budding yeast silent information regulator 2 (Sir2), is a member of the Sirtuin family of NAD + -dependent deacetylases and ADP-ribosyltransferases [ 1 , 2 ]. Accumulating evidence has revealed that Sirt2 plays an important role in multiple cell events [3] , [4] , [5] , which involve a variety of biological and pathological conditions, including development, neural activity, obesity, and carcinogenesis [ 2 , 6 , 7 ]. Accordingly, various Sirtuin inhibitors have been developed and assessed for their effects on different diseases by targeting specific protein structures, biological activities, or signaling pathways [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 ] Additionally, Kim and colleagues have shown that Sirt2 is required for efficient reprogramming of mouse embryonic fibroblasts toward pluripotency. [ 35 ] They demonstrated that depletion of Sirt2 impaired reprogramming efficiency through activation of senescence marker p16. Hence, our findings strongly suggest that the crosstalk between Sirt2‐modulated dynamic changes of the canonical Wnt signaling and Sirt2‐mediated cell reprograming towards pluripotency may play a critical role in determining the proper lineage commitment of kidney stem cells during kidney development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOX2 and KLF4 induced pluripotency without exogenous OCT4 in mouse embryonic fibroblasts (MEFs) and neural progenitor cells [67]. Furthermore, sirtuin 2 was essential for efficiently reprogramming MEFs to naïve states of pluripotency, in contrast to primed pluripotent states [68]. The inhibitors of mitogen-activated protein kinase 1/2 (MAPK1/2) and glycogen synthase kinase-3 and those of cell division protein kinases (cyclin-dependent kinase [CDK] 8/19) presented two approaches for establishing naïve pluripotency [69].…”
Section: Reprogramming Strategies Using Stemness-related Genesmentioning
confidence: 99%